Corporate Tax Policy and Unemployment in Europe: An Applied General Equilibrium Analysis - Leon Bettendorf; Albert van der Horst; Ruud A. de Mooij (Tinbergen Institute, 2007)
This paper analyzes the impact of corporate taxes on structural unemployment, using an applied general equilibrium model for the European Union. We find that the unemployment and welfare effects of corporate taxes differ considerably among European countries. The magnitude of these effects rise in particular in the broadness of the corporate tax base of a country, and the strength of international spillover effects through foreign direct investment. The effect on unemployment is smaller if the substitution elasticity between labour and capital is large, if international spillover effects operate primarily via multinational profit shifting, and if equilibrium forces on the labour market are strong. Although the effect of corporate taxes on unemployment may be smaller than the effect of labour and value-added taxes (e.g. under relatively strong real wage resistance), the welfare costs of corporate taxation are typically larger for most European countries under plausible parameters, especially under strong international spillovers.
Keywords: D58; H25; J64; 330; Corporate Tax; Structural Unemployment; Applied General Equilibrium; European Union; Unternehmensbesteuerung; Arbeitslosigkeit; Allgemeines Gleichgewicht; EU-Staaten